Unveiling Figurative Meaning: In-Depth Investigation into Taylor Swift’s Song ‘Cruel Summer’ - Nabila Mahdafiqya; Anita Dewi Ekawati (Institut Agama Islam Negeri Palopo, 2024)
Taylor Swift's works have been known to have lyrics that are rich in meaning and have hidden figurative meanings, therefore many listeners have difficulty understanding the meaning in the lyrics of her songs and some even interpret them incorrectly. This research is to uncover the hidden figurative meanings in Taylor Swift's